Pengembangan E-LKPD Interaktif Berbasis Liveworksheets dalam Pembelajaran Berdiferensiasi pada Materi Limas Fase D - Cahya, Ine Clarita; Susanto, Susanto; Safrida, Lela Nur; Yudianto, Erfan; Wihardjo, Edy (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
This study aims to develop an interactive e-worksheet (E-LKPD) based on Liveworksheets for differentiated learning on the topic of pyramids (limas) in Phase D that is valid, practical, and effective in improving student learning outcomes. The research employed a development method using the ADDIE model, involving eighth-grade students as subjects. Instruments used include validity, practicality, and effectiveness instruments, with data collected through questionnaires and learning outcome tests. The developed product consists of three E-LKPDs tailored to students’ readiness levels: developing, proficient, and highly proficient. Validation results show an average score of 3.81 out of 4, categorized as very valid. Practicality was measured through teacher and student responses, yielding an average of 76.26%, which falls into the practical category. Effectiveness was assessed based on the learning test results, showing a mastery level of 89%, indicating that the E-LKPD is effective for classroom use. This study is essential due to the growing need for interactive learning materials that accommodate differences in student learning abilities, particularly within the current differentiated learning framework. Moreover, the use of digital tools like Liveworksheets remains underutilized, especially in mathematics topics such as pyramids. This E-LKPD is expected to make learning more engaging and tailored to individual needs, and serve as a foundation for future development of more innovative digital learning materials.